Hot beverages and oesophageal cancer risk in western Kenya: Findings from the ESCCAPE case–control study. Issue 11 (27th January 2019) - Middleton, Daniel RS; Menya, Diana; Kigen, Nicholas; Oduor, Margaret; Maina, Stephen K; Some, Fatma; Chumba, David; Ayuo, Paul; Osano, Odipo; Schüz, Joachim; McCormack, Valerie
Abstract : Oesophageal squamous cell carcinoma (ESCC) has markedly high incidence rates in Kenya and much of East Africa, with a dire prognosis and poorly understood aetiology. Consumption of hot beverages—a probable carcinogen to humans—is associated with increased ESCC risk in other settings and is habitually practiced in Kenya. We conducted a case–control study in Eldoret, western Kenya between August 2013 and March 2018. Cases were patients with endoscopically confirmed oesophageal cancer whose histology did not rule out ESCC. Age and sex‐matched controls were hospital visitors and hospital out and in‐patients excluding those with digestive diseases. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated for self‐reported drinking temperatures; consumption frequency; mouth burning frequency and hot porridge consumption using logistic regression models adjusted for potential confounders. Drinking temperature association with tumour sub‐location was also investigated. The study included 430 cases and 440 controls. Drinkers of 'very hot' and 'hot' beverages (>95% tea) had a 3.7 (95% CI: 2.1–6.5) and 1.4‐fold (1.0–2.0) ESCC risk, respectively compared to 'warm' drinkers. This trend was consistent in males, females, never and ever alcohol/tobacco and was stronger over than under age 50 years. The tumour sub‐location distribution (upper/middle/lower oesophagus) did not differ by reported drinking temperature. Our study is the first comprehensive investigation in this setting to‐date to observe a link between hot beverage consumption and ESCC in East Africa. These findings provide further evidence for the role of this potentially modifiable risk factor in ESCC aetiology. Abstract : What's new? Oesophageal squamous cell carcinoma (ESCC) has markedly high incidence rates in Kenya and much of East Africa, with a dire prognosis and poorly understood aetiology. Hot beverage consumption – a probable carcinogen to humans – is associated with increased ESCC risk in other settings. In this first comprehensive case‐control study to investigate the role of hot beverages in esophageal cancer in Kenya and East Africa, the authors find overall risks of 3.7 and 1.4‐fold for drinking "very hot" and "hot" beverages, respectively, compared to "warm" These findings will contribute to local and global prevention efforts by addressing this potentially modifiable risk factor.